Spatial and temporal variation characteristics and attribution analysis of land water storage changes in China. Issue 11 (19th October 2022) - Zhu, Jiangle; Zhang, Chunsen; Zhang, Jiazheng; Ding, Hao
Abstract: The quantitative study of terrestrial water storage change (TWSC) and its spatial and temporal dynamics has been an important topic in water resources research and management. In this study, we invert the characteristics of TWSC in China based on the GRACE time-varying gravity field model and explore its attribution analysis, using Theil- Sen Median trend, Mann-Kendall test and geographic detector, as well as the geographically and temporally weighted regression model (GTWR), combined with meteorological and drought indicators and other data to analyze the relationship between their drivers. The results are as follows: (1) The influencing factors of TWSC's high effect are minimum temperature, precipitation and maximum temperature, and the explanatory power of TWSC through factor interaction is much higher than that of a single factor; (2) The GTWR model is better than GWR models in determining the relationship between influencing TWSC and drivers, and there are temporal and local differences in the influence of each driver on TWSC; (3) In summer and autumn, the rise of water storage in central China is higher than that in east and west China. In spring and winter, the overall water storage in China shows a deficit, and some regions in Guizhou, Guangdong and Guangxi have a small surplus compared with other regions. HIGHLIGHTS: Innovative research on China's water resources. Using a variety of data and models to invert and analyze water resources. A lot of data download and preprocessing. Use of a variety of impact factors and related indicators to make the results more comprehensive and accurate. Innovative use of seasonal and climate change detailed analysis of the distribution of water resources.